Exodus - Johnstone, W. (Old Testament guides., 1999)
Exodus requires the consideration not only of historical but also of institutional and theological questions. Since such disparate materials have all been brought together into one presentation, it is necessary also to look at the literary function and formulation of the book. In the light of these discussions it is possible to come to a clearer appreciation of the kind of work Exodus is.